Comparative metatranscriptomics reveals extracellular electron transfer pathways conferring microbial adaptivity to surface redox potential changes. Issue 12 (December 2018) - Ishii, Shun'ichi; Suzuki, Shino; Tenney, Aaron; Nealson, Kenneth; Bretschger, Orianna
Abstract Some microbes can capture energy through redox reactions with electron flow to solid-phase electron acceptors, such as metal-oxides or poised electrodes, via extracellular electron transfer (EET). While diverse oxide minerals, exhibiting different surface redox potentials, are widely distributed on Earth, little is known about how microbes sense and use the minerals. Here we show electrochemical, metabolic, and transcriptional responses of EET-active microbial communities established on poised electrodes to changes in the surface redox potentials (as electron acceptors) and surrounding substrates (as electron donors). Combination of genome-centric stimulus-induced metatranscriptomics and metabolic pathway investigation revealed that nineGeobacter/Pelobacter microbes performed EET activity differently according to their preferable surface potentials and substrates. While theGeobacter/Pelobacter microbes coded numerous numbers of multi-hemec- type cytochromes and conductive e-pili, wide variations in gene expression were seen in response to altering surrounding substrates and surface potentials, accelerating EET via poised electrode or limiting EET via an open circuit system. These flexible responses suggest that a wide variety of EET-active microbes utilizing diverse EET mechanisms may work together to provide such EET-active communities with an impressive ability to handle major changes in surface potential and carbon source availability.